Design of management accounting systems in public administration: A case study - Frias, A.; Conceição, A.; Lourenço, C. (European Journal of Applied Business and Management, 2023)
Purpose: Many public entities experience difficulties in designing and implementing a Management Accounting and Control System (MACS). This work aims to design a MACS implementation framework for a public sector organization, constituting a useful tool for other public organizations conducting a similar task. Design/methodology/approach: Following an interventionist research, a comprehensive case study of the organizational and financial structure of the entity under study, as well as the operational activity was carried out. Findings: A framework for designing and implementing a MACS in the public sector is proposed, including a list of main practical difficulties and a roadmap for overcoming them. Research limitations/implications: Since the proposed MACS implementation and cost allocation criteria were developed with the case under investigation in mind, modifying them for use in other organizations is necessary. Practical implications: Professionals in the field acknowledged the model's validity, enhancing the quality of the available data. Originality/value: The implementation of MACS in public sector organizations face several challenges, arising from the complexity that characterizes these organizations. This research adopted a very practical approach, seeking to identify tools to support future MACS design and implementation processes in public organizations.